Etnobotani Ritual Adat Suku Kemak Leimia Di Desa Sadi Kabupaten Belu - Emilia Juliyanti Bria; Aprilia Graselia Naimau; Florian Mayesti Prima R. Makin (JBIOEDRA: Jurnal Pendidikan Biologi, 2023)
The Kemak Leimia Tribe community in Sadi Village is known as one of the famous tribes in Belu Regency. The people of this tribe still use various types of plants in their daily lives, especially in various traditional rituals. The aim of this research is to find out the types of plants used, the parts of the plants used, and how the plants are used in the traditional rituals of this tribe. This research was carried out in March-May 2023 in Sadi Village, East Tasifeto District, Belu Regency. This research uses qualitative and quantitative approaches. The research methods used are interviews, inventory, identification and documentation. The research results show that there are 12 types of plants used in rituals. The most widely used family is the Arecaceae family with 8 plant species in each family used in rituals. The parts of the plant used in the ritual are leaves, fruit, seeds and also contain water. These plants are usually used in rituals such as birth rituals, death rituals, marriage proposals, corn harvest, traditional house feasts, and annual rituals.